Age of top european football players when they started organized training and their value in the transfer market - Metelski, Adam (Quality in Sport, 2023)
There are a few schools of thought about when kids should start playing sports. This study set out to find out when the football players performing at EURO 2020 began trainings in an organized way – on average they were just over 8 years old. The second research issue addressed in this article is the financial value of the players. Football experts, with the support of scientists, do their best to determine the appropriate value of players, and it’s still not easy. The proper valuation of players is an important issue because it influences the management process of football clubs. The study also set out to see if there is a relation between the age of starting to practice in organized way and the subsequent value of the athlete? A univariate regression analysis was performed, in which the dependent variable was player value, and the independent variable was the age of the athlete when he started to play football in organized way. Based on the regression coefficients, it can be concluded that players who started at younger ages now show a higher level of value. In conclusion, the results show how demanding professional sport is and at what age a person needs to make the right decisions to be able to think about being a professional footballer.